Induction of autoimmune diabetes in non‐obese diabetic mice requires interleukin‐21‐dependent activation of autoreactive CD8+ T cells. (4th July 2013) - Chen, X.‐L.; Bobbala, D.; Rodriguez, G. M.; Mayhue, M.; Chen, Y.‐G.; Ilangumaran, S.; Ramanathan, S.
Summary Non‐obese diabetic (NOD) mice lacking interleukin (IL)‐21 or IL‐21 receptor do not develop autoimmune type 1 diabetes (T1D). We have shown recently that IL‐21 may promote activation of autoreactive CD8+ T cells by increasing their antigen responsiveness. To investigate the role of IL‐21 in activating diabetogenic CD8+ T cells in the NOD mouse, we generated IL‐21‐deficient NOD mice expressing the highly pathogenic major histocompatibility complex (MHC) class‐I‐restricted 8.3 transgenic T cell receptor (TCR). IL‐21 deficiency protected 8.3‐NOD mice completely from T1D. CD8+ T cells from the 8.3‐NOD.Il21−/− mice showed decreased antigen‐induced proliferation but displayed robust antigen‐specific cytolytic activity and production of effector cytokines. IL‐21‐deficient 8.3 T cells underwent efficient homeostatic proliferation, and previous antigen stimulation enabled these cells to cause diabetes in NOD.Scid recipients. The 8.3 T cells that developed in an IL‐21‐deficient environment showed impaired antigen‐specific proliferation in vivo even in IL‐21‐sufficient mice. These cells also showed impaired IL‐2 production and Il2 gene transcription following antigen stimulation. However, IL‐2 addition failed to reverse their impaired proliferation completely. These findings indicate that IL‐21 is required for efficient initial activation of autoreactive CD8+ T cells but is dispensable for the activated cells to develop effector functions and cause disease. Hence, therapeutic targeting of IL‐21 in T1D may inhibit activation of naive autoreactive CD8+ T cells, but may have to be combined with other strategies to inhibit already activated cells.